Analisis Fiqh Siyasah Terhadap Kampanye Pemilihan Umum Di Media Sosial Berdasarkan Peraturan Komisi Pemilihan Umum Nomor 23 Tahun 2018 Tentang Kampanye Pemilihan Umum - Muhammad Fadhli (Siyasah Wa Qanuniyah, 2023)
Based on the General Election Commission Regulation (PKPU) of the Republic of Indonesia No. 23 of 2018 on Election Campaigns, Article 35 paragraphs 1 to 4 regulates campaigns on social media. Paragraph 1 states, "Election participants may conduct campaigns through social media as referred to in Article 23 paragraph (1) letter e." Social media is widely used to disseminate information, often without verifying its accuracy, and is prone to fake news and hate speech. The increasing use of social media in Indonesia reflects its growing influence. This study examines: 1) How election campaigns on social media are regulated under PKPU No. 23 of 2018, and 2) How these campaigns align with Fiqh Siyasah. The qualitative research adopts a library research method with a descriptive-analytical approach, using secondary sources like legal texts and academic references. The findings reveal that PKPU No. 23 of 2018 requires participants to register official campaign accounts, limiting them to a maximum of ten accounts per platform. These accounts must be registered no later than one day before the campaign period starts and deactivated on the last day. From the Fiqh Siyasah perspective, social media campaigns are permissible if they avoid slander, adhere to ethical values, and comply with regulations like PKPU No. 23 of 2018. The regulation supports the effective dissemination of campaign information, such as candidates’ visions and missions, while minimizing falsehoods, hate speech, and other violations. This ensures campaigns align with Islamic principles, focusing on public benefits (maslahah). Anything promoting maslahah is permissible in Islam, showing how the regulation fosters positive outcomes for society. PKPU No. 23 of 2018 demonstrates the compatibility between ethical governance and Fiqh Siyasah, balancing modern electoral practices with Islamic values.